Equine proliferative enteropathy – a review of recent developments - Pusterla, N. (Equine Vet J, 2013)
Equine proliferative enteropathy (EPE) is a disease of foals caused by the obligate intracellular organism Lawsonia intracellularis. This emerging disease affects mainly weanling foals and causes fever, lethargy, peripheral oedema, diarrhoea, colic and weight loss. The diagnosis of EPE may be challenging and relies on the presence of hypoproteinaemia, thickening of segments of the small intestinal wall observed upon abdominal ultrasonography, positive serology and molecular detection of L. intracellularis in faeces. Although the clinical entity, diagnostic approach and treatment of EPE are well established and described, the epidemiology for this disease has remained largely unaddressed. This article focuses on new developments in the field of EPE, including epidemiology, pathophysiology, clinical signs, diagnosis, treatment and prevention. The Summary is available in Chinese – see Supporting information.